Economic Diversification in Nigeria: The Prospect of Tourism - AHMED, Ayodele Victor; ADAMA, Joseph Ibrahim; OBASAJU, Olusegun Barnabas; ASALEYE, Abiola John; OWA, Grace Tijesu (Journal of Environmental Management and Tourism, 2019)
In recent times, the economic fortune of Nigeria has been dwindling as a result of a drastic fall in the price of oil in the world market coupled with the illegal bunkering and the Niger/Delta militancy. This calls for the need to diversify the economy. Tourism is one sector that can guarantee numerous benefits for a sustainable growth from the over reliance on the oil sector. This paper therefore, examined the prospect of tourism as a source of income generation, foreign exchange earner and a source of employment. The sources of data were secondary gotten from CBN Statistical Bulletin and the World Tourism Organization. The paper examined the relationship between tourism and economic growth using Least Square. The result revealed that there is a significant relationship between tourism and economic growth. This confirmed the tourism led growth hypothesis that tourism triggers economic growth because tourists’ spending provides foreign exchange earnings and job opportunities. It follows that if well annexed, tourism can serve as a good alternative to oil reliability thereby bringing an end to Nigeria’s over dependence on oil with the attendance volatility. The paper recommended provision of infrastructural facilities and improvement in security in order to motivate prospective tourists.